FALDI‐based criterion for and the origin of an electron density bridge with an associated (3, –1) critical point on Bader's molecular graph. Issue 27 (14th October 2018) - de Lange, Jurgens H.; van Niekerk, Daniël M. E.; Cukrowski, Ignacy
Abstract : The total electron density (ED) along the λ 2 ‐eigenvector is decomposed into contributions which either facilitate or hinder the presence of an electron density bridge (DB, often called an atomic interaction line or a bond path). Our FALDI‐based approach explains a DB presence as a result of a dominating rate of change of facilitating factors relative to the rate of change of hindering factors; a novel and universal criterion for a DB presence is, thus, proposed. Importantly, facilitating factors show, in absolute terms, a concentration of ED in the internuclear region as commonly observed for most chemical bonds, whereas hindering factors show a depletion of ED in the internuclear region. We test our approach on four intramolecular interactions, namely (i) an attractive classical H‐bond, (ii) a repulsive O⋅⋅⋅O interaction, (iii) an attractive Cl⋅⋅⋅Cl interaction, and (iv) an attractive CH⋅⋅⋅HC interaction. (Dis)appearance of a DB is (i) shown to be due to a "small" change in molecular environment and (ii) qualitatively and quantitatively linked with specific atoms and atom‐pairs. The protocol described is equally applicable (a) to any internuclear region, (b) regardless of what kind of interaction (attractive/repulsive) atoms are involved in, (c) at any level of theory used to compute the molecular structure and corresponding wavefunction, and (d) equilibrium or nonequilibrium structures. Finally, we argue for a paradigm shift in the description of chemical interactions, from the ED perspective, in favor of a multicenter rather than diatomic approach in interpreting ED distributions in internuclear regions. © 2018 Wiley Periodicals, Inc. Abstract : A novel quantum chemical function is introduced which can be used to study and understand the presence or absence of a density bridge in an internuclear region. The CP (r ) function uses the gradients of bonding, nonbonding, and antibonding density contributions from the FALDI density decomposition scheme to assess the origin and nature of density bridges for intermolecular and intramolecular interactions in equilibrium and nonequilibrium structures.